Topicalization of the Dawan Language Mollo Dialect - A . Nau, Ariyanto; Semiun, Agustinus; Semiun, Agustinus; Kroon, Yosep B. (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl July, 2021)
This research studies about topicalization of the Dawan language Mollo Dialect. The problems of this research are namely 1) is there any topic sentence in Dawan Language? 2) how is the topic sentence structure in Dawan Language?. The research located in Oelbubuk village, middle Mollo district, South Eastern Timor Regency, East Nusa Tenggara Province. This research is qualitative research. The data were taken from folklore text The methods used to collect the data were interview, observation and introspection. The technique used in this research are the disappearing technique, reverse technique, insertion technique, and chancing technique. The result of data analysis is an informal way by verbal description. The pragmatic theory is applied in data analysis. The result of this research is indicated that there is a topicalization structure in Dawan Language. Preposition es always appear in topicalization in Dawan Language as distinguished future of active voice structure and topic sentence. The appearance of clitic is also attached to the verb as a structure of a topic sentence in Dawan Language.